Peningkatan Hasil Belajar (IPAS) Materi Indonesiaku Kaya Budaya Dengan Model Problem Based Learning pada Siswa Kelas V C di SDN 009 Sungai Kunjang - Renianti Ranti Asmira; Tri Wahyuningsih; Khusnul Khotimah; Andi Asrafiani Arafah (Mataram University, 2026)
This study aimed to determine the improvement of students’ learning outcomes in IPAS on the topic “Indonesiaku Kaya Budaya” through the implementation of the Problem Based Learning (PBL) method for fifth-grade students at SDN 009 Sungai Kunjang in the 2024/2025 academic year. This research employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of three meetings. The research procedure included four stages: planning, implementation, observation, and reflection. The subjects of this study were 26 students of class V C at SDN 009 Sungai Kunjang. Data collection techniques included teacher activity observation sheets, student activity observation sheets, and learning outcome tests. Data analysis techniques used average scores, percentages, and diagrams. The results showed that students’ learning outcomes improved significantly after the implementation of the Problem Based Learning method. In the pre-cycle stage, the average score was 68.38 with a mastery percentage of 34%. In Cycle I, the mastery percentage increased to 61.53%. In Cycle II, the average score increased to 84.34 with a mastery percentage of 84.61%, where 22 students achieved mastery learning. These results exceeded the predetermined success indicator of 75%. Therefore, it can be concluded that the Problem Based Learning method effectively improved students’ learning outcomes in IPAS on the topic “Indonesiaku Kaya Budaya.”